The hyperbola above has equation
2
x
2
+
1
0
x
y
+
8
y
2
+
4
x
+
2
y
+
1
=
0
.
Let m 1 and m 2 be the slopes of the asymptotes (shown in green) such that ∣ m 1 ∣ > ∣ m 2 ∣ , and let m 3 be the slope of the line that passes through both points, where the tangents have infinite slopes.
Find the value of ∣ m 1 ∣ − ∣ m 2 ∣ − ∣ m 3 ∣ 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let V 1 and V 2 be the vertices of the hyperbola, let t 1 and t 2 be the tangents to the hyperbola at V 1 and V 2 , and let ℓ be the line passing through V 1 and V 2 . You assume that t 1 and t 2 are vertical (by taking the line with slope of infinity), but they are not.
Because of the x y term, the hyperbola is slightly rotated, so ℓ is not perfectly horizontal. But ℓ and t 1 are perpendicular, so t 1 is not perfectly vertical (and the same for t 2 ).
We can calculate m 3 as follows. We know that m 1 = − 1 and m 2 = − 4 1 . Let α be the angle between the line with slope m 1 and the x -axis, so tan α = 1 . Let β be the angle between the line with slope m 2 and the x -axis, so tan β = 4 1 .
Let θ be the angle between ℓ and the x -axis. Note that ℓ bisects the asymptotes, so θ = 2 α + β and m 3 = − tan θ .
Note that tan 2 θ = tan ( α + β ) = 1 − tan α tan β tan α + tan β = 3 5 . But tan 2 θ = 1 − tan 2 θ 2 tan θ , so 1 − tan 2 θ 2 tan θ = 3 5 . Solving for tan θ , we get tan θ = 5 − 3 ± 3 4 .
Since m 3 = − tan θ is negative, m 3 = 5 3 − 3 4 .
Problem Loading...
Note Loading...
Set Loading...
By implicit differentiation of 2 x 2 + 1 0 x y + 8 y 2 + 4 x + 2 y + 1 = 0 , we can calculate f ′ ( x ) as:
4 x + 1 0 ( y + x ⋅ f ′ ( x ) ) + 1 6 y ⋅ ( f ′ ( x ) ) + 4 + 2 ( f ′ ( x ) ) = 0
f ′ ( x ) ⋅ ( 1 6 y + 1 0 x + 2 ) = − 1 0 y − 4 x − 4
f ′ ( x ) = 8 y + 5 x + 1 − ( 5 y + 2 x + 2 )
Upon the vertices of the hyperbola, the tangents touching them will have the slope of infinity as the x-values approach local minimum and maximum. Therefore, for infinite slope, the denominator of f ′ ( x ) reaches 0 : 8 y + 5 x + 1 = 0 is the line passing through these vertices.
Then y = − 8 5 x − 8 1
Thus, m 3 = − 8 5 .
Now for the two asymptotes, we know that the slope of these lines will touch the hyperbola as the x-values reach plus or minus infinity, so we can apply the limit to f ′ ( x ) :
lim x → ∞ f ′ ( x ) = lim x → ∞ 8 y + 5 x + 1 − ( 5 y + 2 x + 2 )
And ( 8 − 5 ) ( 8 y + 5 x + 1 ) = − 5 y − 8 2 5 x − 8 5
Hence, by polynomial division,
lim x → ∞ f ′ ( x ) = lim x → ∞ [ 8 − 5 + 8 y + 5 x + 1 8 2 5 x + 8 5 − 2 x − 2 ] = lim x → ∞ [ 8 − 5 + 8 y + 5 x + 1 8 9 x + 8 − 1 1 ]
Then, from the equation, we can solve for y-value as the following:
8 y 2 + ( 1 0 x + 2 ) y + ( 2 x 2 + 4 x + 1 ) = 0
y = 2 ⋅ 8 − ( 1 0 x + 2 ) ± ( 1 0 x + 2 ) 2 − 4 ⋅ 8 ⋅ ( 2 x 2 + 4 x + 1 ) = 8 − ( 5 x + 1 ) ± 9 x 2 − 2 2 x − 7
Thus, 8 y + 5 x + 1 = ± 9 x 2 − 2 2 x − 7 .
As a result, lim x → ∞ [ 8 − 5 + 8 y + 5 x + 1 8 9 x + 8 − 1 1 ] = lim x → ∞ [ 8 − 5 ± 9 x 2 − 2 2 x − 7 8 9 x + 8 − 1 1 ]
The square root result of 9 x 2 − 2 2 x − 7 will have a highest degree of 3 x , and as x approaches infinity, the values of other lesser degrees will be so infinitesimal and, thereby, negligible.
Thus, lim x → ∞ [ 8 − 5 ± 9 x 2 − 2 2 x − 7 8 9 x + 8 − 1 1 ] = lim x → ∞ [ 8 − 5 ± 3 x 8 9 x + 8 − 1 1 ] = 8 − 5 ± 8 3 = 4 − 1 or − 1
Hence, ∣ m 1 ∣ = 1 ; ∣ m 2 ∣ = 4 1 .
Finally, ∣ m 1 ∣ − ∣ m 2 ∣ − ∣ m 3 ∣ 1 = 1 − 4 1 − 8 5 1 = 8 .